Se souvenir du tribun et de l’apôtre. John Ruskin par son traducteur Émile Cammaerts (1878-1953) - Julie Lageyre (Cahiers Victoriens et Edouardiens)
Émile Cammaerts (1878–1953) was a Belgian poet, journalist and dramatist. He was one of the most important translators of John Ruskin in French. Between 1906 and 1916, he published for instance the translations of Lectures on Architecture and Painting (1910), Val d’Arno (1911) and a section of the Modern Painters (1914). Cammaerts searched for a balance between the correct transposition of John Ruskin’s writings and the required adjustments for a Francophone audience. Among the translators of Ruskin, Cammaerts distinguished himself by a singular mediation based on the demonstration of the connection between art and religion. He introduced to the French audience a religious Ruskin, moralist as much as artist, and even socialist. But the reception of these translations was not limited to the diffusion of Ruskin’s writings across the Channel. The interpretation of Ruskin’s theories was used for the construction of national artistic traditions in France and Belgium.